N, P AND K NUTRITION UPTAKE AND GROWTH OF SOYBEAN (Glycine max) PLANTS ON INORGANIC FERTILIZER TREATMENT AND TYPES OF MANURE - Muhammad Rizwan; Diapari Siregar; Haris Paddilah; Nurhayati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This research was carried out in Laut Tador Village, Sei Suka District, Batu Bara Regency, North Sumatra Province. This place is at an altitude of ±25 meters above sea level (masl), with flat topography. This research was carried out from November 2021 to February 2022. This research aims to determine the dose of inorganic fertilizer and types of manure on N, P and K nutrient uptake and on the growth of soybean plants (Glycine max). This research began in October 2021 to February 2022. Factorial pattern research with a factorial Randomized Block Design/RAK. Treatment factors use various types of manure (O) as the first factor and the second factor is the application of inorganic fertilizer (A). The results of soil analysis on the experimental land are generally low, indicated by the organic matter content at the location, namely 0.25%, not reaching 3% according to ideal soil conditions. . Research Results: The type of manure treatment had a significant effect on the number of primary branches, plant height, stem diameter, crown dry weight, number of root nodules, root nodule weight, while the interaction of organic and anoragnic fertilizers had no significant effect on the number of primary branches, plant height and nutrient uptake. . Providing chicken manure at a dose of 15 tons ha produced the highest number of primary branches, plant height, stem diameter, crown dry weight, number of root nodules, and root nodule weight.